Topotactic Mechanisms Related to the Graphene Planes: Chemical Intercalation of Electron Donors into Graphite. Issue 45 (19th November 2019) - Cahen, Sébastien; Speyer, Lucie; Lagrange, Philippe; Hérold, Claire
Abstract : The intercalation of electron donor species into graphite belongs to the class of two‐dimensional topotactic reactions. During the intercalation, which requires an oxido‐reduction between the reagents, the graphene planes, which form the skeleton of the host material, remain indeed quasi unaltered while their spacing is strongly expanded allowing the setting up of the guest reagent layers. Intercalation into graphite is therefore the prototype of the topotactic reaction. The intercalation mechanisms of these electron donors such as metals, metallic alloys and metal combinations (molecules, electronegative elements) have been significantly studied at length. They are especially numerous and greatly diversified. In this paper, we do not aim to depict all the known graphite intercalation compounds but to draw up an inventory of the whole of these mechanisms. The latter are systematically illustrated by means of several characteristic examples for each one. This significant diversity appears as a remarkable distinctive feature of graphite as host lamellar material. Abstract : All mechanisms of intercalation of electron donors into graphite by various methods are systematically listed. These topotactic reactions lead to layered compounds showing unexpected chemical and physical properties and appearing often as quantum materials (superconductivity, magnetic order). They also have interesting applications (electrodes for Li‐ion batteries).